2020
DOI: 10.1038/s41467-020-19699-5
|View full text |Cite
|
Sign up to set email alerts
|

RNA structure-wide discovery of functional interactions with multiplexed RNA motif library

Abstract: Biochemical assays and computational analyses have discovered RNA structures throughout various transcripts. However, the roles of these structures are mostly unknown. Here we develop folded RNA element profiling with structure library (FOREST), a multiplexed affinity assay system to identify functional interactions from transcriptome-wide RNA structure datasets. We generate an RNA structure library by extracting validated or predicted RNA motifs from gene-annotated RNA regions. The RNA structure library with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…There are rich biological insights delivered by the layer 2 features already, which also significantly influence the translation rate (Supplementary Figure 3). Among the top important layer 2 motifs, ‘UUUCC‘ and ‘GCGGC‘ are found to impact protein-RNA interaction[29], and ‘UGGGU‘ impacts the secondary structure of the RNA [30, 31], a known regulatory factor of the translation process.…”
Section: Resultsmentioning
confidence: 99%
“…There are rich biological insights delivered by the layer 2 features already, which also significantly influence the translation rate (Supplementary Figure 3). Among the top important layer 2 motifs, ‘UUUCC‘ and ‘GCGGC‘ are found to impact protein-RNA interaction[29], and ‘UGGGU‘ impacts the secondary structure of the RNA [30, 31], a known regulatory factor of the translation process.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the motif types of uPRA genes are quite diverse by in silico analysis ( Table S7 ), and several different combinations of RNA-binding proteins might be involved in the maintenance of iPSCs. For future screening of the binding motif of individual RNA in each cell type, cross-linking and immunoprecipitation (CLIP) ( Ule et al., 2003 ) or folded RNA element profiling with structure library (FOREST) ( Komatsu et al., 2020 ) should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the possibility of rG4 folding during the process of cell fixation and visualization cannot be completely ruled out. Furthermore, rG4 antibodies such as BG4, which has been widely used for detecting rG4s in cells 21 , have been shown to cross-react with non-G4 sequences 23 . Thus, these studies are unable to determine the fraction of rG4 sequences that fold into rG4 structures.…”
Section: Main Textmentioning
confidence: 99%